Using core samples of a Nordic seabird nest to infer pelagic fish stock around Iceland - Brynja Onus 1988- (2017)
The marine environment of the North Atlantic has seen some fluctuations that result in variation of abundance and distribution of pelagic fish. This variation has been observed in Iceland by the collapse of the herring stock in the 1960’s as well as the recent introduction of mackerel in 2007. An attempt to observe these fluctuations through the use of core sampling of northern gannets was performed on the colonies at Hellisey and Skrúður. The nest composition was also recorded through dry weight with earth and stones being the most abundant material. The results yielded few fish debris, with the exception of several fish vertebrae and one otolith. Most of the material was found at the surface layer of the core indicating a dissolving effect of the slightly acidic bird nest.